Decoding of periodontal screening and recording index - Dler Ali Kursheed; Faraedon Mohidden Zardawi; Hadi Mohammad Ismail; Aras Maruf Rauf; Sarhang Sarwat Gul (Erbil Dental Journal, 2021)
Background and Objective: This study based on decoding of the original periodontal screening and recording (PSR) index by adding some additional clinical variables and preserving its simplicity. This study aimed to decode PSR index to reveal all the percentage of variables masked by each code in PSR index. Methods: In this interventional clinical study, PSR criteria were obtained from 50 participants plus decoding of each PSR code such as percentage of bleeding (Bl), calculus (Cal) and pocket depth (PD) in each sextant. Further modification of PSR was involved adding few extra variables such as stain (St), over-hanged restorations (Ov) and crowding (Cr) to each sextant. The average of PSR codes and following decoding in each subject was calculated and compared to show the percentage of masking. The study was conducted in B&R Dental Center (March-October 2019). Results: PSR index and decoding of the variables were collected from 50 subjects. PSR code 2 was the most prevalent code (62.61%) followed by code 1 (16.83%) and code 3 (10.1%). Furthermore, BI, St, Cal and Ov were the most frequent variables recorded among all sextants. Decoding of code 2, showed that 76.8% of BI was masked by PSR index. Whereas, PSR code 3 masked 96.2% of variables of PSR code 1 and 2 (BI, stain, calculus, over-hanged restoration and crowding). Finally, 98.6% of variables in PSR code 1, 2 and 3 were masked by PSR code 4. Conclusions: Decoding the PSR index by exposing the masked variables and adding few new variables will develop more informative and inclusive system of examination and diagnosis along with keeping the simplicity of the other indices of periodontal screening such as PSR index.